Inventory management: proposal for improvements in a motorcycle parts store (Research, Society and Development, 2023)
This research proposes structured improvements in inventory management for a company that operates in the retail of motorcycle parts, in this way the Ishikawa diagram was used to identify the root causes of failures in inventory management, detailing them in 6M's so that after it was possible propose solutions integrating ABC classification, reorder point model and periodic replenishment. After identifying the causes, action plans were started where the ABC classification was applied to identify the most important materials in terms of value and demand. From the classification of the items, the replenishment model per reorder point was applied to determine the ideal replenishment quantity and the Periodic replenishment model to check the stock level at the time of revision and order a batch with sufficient quantity to replenish the stock at the maximum projected level, to demonstrate the application of replacement models, data from a class A item that corresponds to lubricating oil was used. The results of the study showed that the integration of the ABC classification and the order point and periodical replenishment models prove to be effective in inventory management. The study concludes that inventory management using ABC classification tools, order point replenishment model and periodic replenishment model can be applied in different sectors and industries to solve inventory problems. Studies like this one can help companies better manage their inventories, reduce costs and improve customer satisfaction.